Sigilo Jornalístico e Segredo de Estado - Romano, Roberto (Revista Entreideias: educação, cultura e sociedade, 2006)
Abstract: The text analizes the problem of secret in state and society nowadays. It discusses the problem from a particular case, the proposal of reduction of journalistic sources secrecy. From a political, historic and philosophical bibliography the author presents the basic thesis of governamental accountability, an essential concept of democratic order, that indicates the responsabilities of those who rules the government, in face of sovereign people, whaterever be its level, time and space. The author shows that concept of accountability is losing substance in world, announcing bitter time to citizenship. Key words: Accountability; Secret; Democracy; Transparency; Citizenship.